Copper-catalyzed formation of indolizine derivatives via one-pot reactions of chalcones, benzyl bromides and pyridines. Issue 33 (14th August 2020) - Li, Chao-dong; Tang, Xue; He, Xiao-long; Xue, Shuai; Xu, Jiang-hong; Li, Yu-jin
Abstract: The one-pot cascade reaction for the preparation of indolizine from a wide range of chalcone, pyridine and benzyl bromide via [3 + 2] cycloaddition/oxidative aromatization promoted by Cu(OAc)2 has been developed. This convenient method don't need to isolate the intermediates and the desired products indolizines were obtained in moderate to high yield catalyzed by Cu(OAc)2 in the presence of oxygen. Graphical abstract: Image 1 Highlights: a one-pot manner for synthesis of indolizines derivatives, without purifying or isolating the intermediates. The reaction doesn't require the addition of starting materials stage by stage and no additional separation process was required. It is a new method for the synthesis of the desired products indolizines in high yield with catalyzed by Cu(OAc)2 in the presence of oxygen.